The Myth of the Born Criminal : Psychopathy, Neurobiology, and the Creation of the Modern Degenerate - Jalava, Jarkko, 1970-; Griffiths, Stephanie; Maraun, Michael, 1963- (Book collections on Project MUSE., 2015)
A stunning merger of rigorous science and clear-sighted cultural analysis, The Myth of the Born Criminal is for anyone who wonders just what truth - or fiction - lurks behind the study of psychopathy.